Analysis of Human Resources Management in Improving Learning Strategies at MAN 2 Situbondo During the Covid-19 Pandemic - Turmudi, Imam (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The objective of this study was to ascertain the learning strategies employed in the context of the New Normal Era. In recent years, Indonesia has been particularly affected by the global pandemic of the novel coronavirus, which has precipitated a profound transformation in all aspects of life. The field study was conducted at the Madrasah Aliyah Negeri 2 Situbondo institution, as it was deemed an appropriate setting in which to observe and analyse teaching and learning processes, and to identify strategies that facilitate ongoing learning. This study employs a qualitative descriptive analysis strategy. In the context of the new normal era, human resource management plays a pivotal role in enhancing learning techniques through concerted efforts, a well-considered approach, and a systematic debriefing process. This is particularly evident in the area of information technology abilities and virtual learning habits, as evidenced by the survey results. In the context of the new normal period, the most effective learning method is to adhere to the regulations set forth by the Ministry of Education and Culture regarding virtual learning on an approved platform. To reduce misunderstandings between teachers and students, it is essential that both parties have the necessary tools, credentials, and awareness of the factors that will determine the course of learning. In order to prevent dishonesty, laziness, and cheating on tests, students study at home under the guidance and supervision of their parents, thereby maintaining the standards of ethics, morals, and norms in academia.